Asymptomatic COVID-19 patients: a threat to an active otolaryngologist - Nagi, Ravinder Singh; Singh, Satinder Pal; Duggal, Prahlad (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
A new virus was reported for causing a spurt of pneumonia cases in Wuhan, Hubei 56 province in China in December 2019. This coronavirus, was initially named as the 2019- novel coronavirus (2019-nCoV) on 12 January 2020 by World Health Organization (WHO). WHO officially named the disease as coronavirus disease 2019 (COVID- 19) and coronavirus study group (CSG) of the International Committee proposed to name the new Coronavirus as SARS-CoV-2, both issued on 11 February 2020.